1991
DOI: 10.1039/c39910000656
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of lanthanide(III) complexes of the bis(propylamide) of diethylenetriaminepentaacetic acid in aqueous solution

Abstract: NMR shift and relaxation measurements show that the lanthanide(iii) complexes of the bis(propy1amide) of diethylenetriaminepentaacetic acid (H3L) occur in at least eight isomeric forms, in which the metal ion is coordinated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…60 cm À1 to lower energy were observed for the carbonyl stretching frequencies upon complexation, indicating amide oxygen coordination to gadolinium(III) ion. These findings are consistent with previous studies which have shown that DTPA bisamide derivatives coordinate to lanthanide(III) ions via three acetate oxygens, three nitrogen atoms and two carbonyl oxygens of the amide group, while the ninth coordination site is occupied by a water molecule (Geraldes et al 1991;Ehnebom et al 1992;Bligh et al 1995;Aime et al 1997;Wang et al 1999).…”
Section: Resultssupporting
confidence: 93%
“…60 cm À1 to lower energy were observed for the carbonyl stretching frequencies upon complexation, indicating amide oxygen coordination to gadolinium(III) ion. These findings are consistent with previous studies which have shown that DTPA bisamide derivatives coordinate to lanthanide(III) ions via three acetate oxygens, three nitrogen atoms and two carbonyl oxygens of the amide group, while the ninth coordination site is occupied by a water molecule (Geraldes et al 1991;Ehnebom et al 1992;Bligh et al 1995;Aime et al 1997;Wang et al 1999).…”
Section: Resultssupporting
confidence: 93%
“…The number of resonances in NMR spectra at low temperature shows that all of these isomers are populated in aqueous solution (see Figure 5.5) [197,198,210]. On an increase in temperature, coalescence of pairs of resonances has been observed due to the isomerization processes through the wagging and decoordination-coordination mechanisms.…”
Section: The Parent System Dtpa and Dtpa-bisamidesmentioning
confidence: 95%
“…Experimental settings: spectral width 10000 Hz, 90°pulse (7 µs), acquisition time 10 ms, 1000 scans and no sample spinning. Aqueous solutions containing 2.6% of 17 O isotope (Yeda, Israel) were used. The observed transverse relaxation rates (R O 2obs ) were calculated from the signal width at half-height (∆ν 1/2 ): R O 2obs ϭ π ∆ν 1/2 .…”
Section: Synthesis Of Gdmentioning
confidence: 99%
“…Variable temperature 17 O NMR measurements were recorded at 2.1 T on a JEOL EX-90 spectrometer, equipped with a 5 mm probe, by using a D 2 O external lock. Experimental settings: spectral width 10000 Hz, 90°pulse (7 µs), acquisition time 10 ms, 1000 scans and no sample spinning.…”
Section: Synthesis Of Gdmentioning
confidence: 99%